Implementation of K3 and Biosecurity in Freshwater Fish Cultivation in Bungalawang Village, Tabukan Tengah District: Implementation of K3 and Biosecurity in Freshwater Fish Cultivation - darna; Karimela, Ely Jhon; Tomasoa, Aprelia M. (Sam Ratulangi University, 2025)
Bungalawang Village, located in Tabukan Tengah District, Sangihe Islands, and tilapia is one of the types of fish that is commonly cultivated. Tilapia has economic value, fast growth, and good reproduction. In addition to tilapia, several other freshwater fish species are cultivated, including pomfret, catfish, and eel. Bungalawang Village has the potential to developing land cultivation businesses, and tilapia is the primary choice for the community. Demand for consumption, especially tilapia, is increasing daily, but the availability of seeds and fish for consumption remains a challenge and constraint. Therefore, fish farmers in Bungalawang Village are striving to improve freshwater fish cultivation. As a K3 is an effort to create a workplace that is safe, healthy and free from environmental pollution so that it can reduce or be free from work accidents and thus increase work productivity. Biosecurity is all actions, procedures and policies to prevent the entry and spread of pathogens such as bacteria, viruses, fungi and parasites in fish production facilities for hatchery, rearing and maintaining fish. The community service program of excellence aims to assist fish farmers in Bungalawang village in implementing of occupational health and safety (K3) and biosecurity in freshwater fish cultivation. The objectives PMUP can are achieved through education and training of K3 and biosecurity implementation, water management and quality, selecting superior seeds and broodstock, and controlling fish pests and diseases. ABSTRAK Kampung Bungalawang, terletak di Kecamatan Tabukan Tengah, Kepulauan Sangihe, dan ikan nila merupakan salah satu jenis ikan yang umum dibudidayakan. Ikan nila memiliki nilai ekonomis, pertumbuhannya cepat, dan perkembangbiakan yang baik. Selain ikan nila, ada beberapa jenis ikan air tawar yang dibudidayakan yaitu bawal, lele, dan sidat. Kampung Bungalawang memiliki potensi untuk pengembangan usaha budidaya darat, dan ikan nila menjadi pilihan utama bagi masyarakatnya. Permintaan konsumsi, terutama ikan nila, semakin hari meningkat, namun ketersediaan benih dan ikan konsumsi masih menjadi tantangan dan kendala. Oleh karena itu, pembudidaya ikan di kampung Bungalawang berupaya melakukan perbaikan dalam budidaya ikan air tawar. K3 adalah upaya menciptakan tempat kerja yang aman, sehat, dan bebas dari pencemaran lingkungan sehingga dapat mengurangi atau bebas dari kecelakaan kerja sehingga dapat meningkatkan produktivitas kerja. Biosecurity adalah segala tindakan, prosedur dan kebijakan untuk mencegah masuk dan menyebarnya pathogen seperti bakteri, virus, jamur maupun parasit pada fasilitas produksi pembenihan, pembesaran, dan pemeliharaan ikan. Kegiatan Pengabdian kepada Masyarakat Unggulan Program Studi bertujuan untuk membantu masyarakat pembudidaya ikan di kampung Bungalawang tentang penerapan K3 dan biosecurity dalam budidaya ikan air tawar. Tujuan PMUP ini dapat dicapai lewat edukasi dan pelatihan penerapan K3 dan biosecurity, manajemen dan kualitas air, memilih benih dan induk unggul, dan penanggulangan hama penyakit ikan